Spatiotemporal evolution and driving factors of eco-environmental quality in the Beijing-Tianjin-Hebei urban agglomeration in China - Lemeng Liu; Jinghua Long; Wei Zhang; Jintian Yang (Scientific Reports)
Abstract This study utilized Google Earth Engine (GEE) to compute the Remote Sensing Ecological Index (RSEI) and assess the spatiotemporal evolution of eco-environmental quality in the Beijing-Tianjin-Hebei (BTH) urban agglomeration from 2000 to 2020. Additionally, Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to examine how climatic, topographical, urbanization, soil, and biological factors influenced eco-environmental quality dynamics. The results showed that from 2000 to 2020, RSEI exhibited a fluctuating decline, with the proportion of areas having the highest RSEI dropping from 7.99% in 2000 to 1.20% in 2020, while regions with poor and worst RSEI levels followed a fluctuating upward trend, rising from 4.80 to 15.89%. NDVI emerged as the dominant driver of RSEI in the BTH urban agglomeration, with its contribution to the principal components peaking in 2000 and exhibiting a fluctuating downward trend thereafter until 2020. In 2015, LST turned positive in PC1 and similarity dropped, indicating a shift in ecological mechanisms. During this period, the ranking of key influencing factors was biological > climatic > soil > topographical > urbanization. Furthermore, the spatial distribution of RSEI exhibited distinct clustering patterns, with H–H regions mainly located in the Bashang Plateau in northern BTH, while L-L regions were concentrated in the southeastern plains, gradually expanding from scattered points to more continuous areas.